Efficacy of an intranasally administered live attenuated PRRSV-2 vaccine against challenge with a highly virulent PRRSV-1 strain - Mateu, E.; Cortey, M.; Serena, M. S.; Domingo-Carreño, I.; Alberch, M.; Aguirre, L.; Diaz, I.; Martín, M.; Sanchez-Carvajal, J. M.; Rodriguez-Gomez, I. M.; Lara-Puente, J. H.; Artigas-Cabre, C.; et al. (Frontiers in Veterinary Science, 2025)
IntroductionThe emergence of highly virulent strains of the porcine reproductive and respiratory syndrome virus has driven the need for new vaccines. This study evaluates the efficacy of an intranasal (IN) vaccine composed of a naturally attenuated PRRSV-2 isolate, compared to a commercially available intramuscularly administered (IM) PRRSV-1 vaccine, against a heterologous challenge with a highly virulent PRRSV-1 strain (R1).MethodsSixty-eight PRRSV-naïve pigs were divided into four groups: two non-vaccinated controls (NV/NCh, NV/Ch), one IM-vaccinated with a PRRSV-1 MLV (Por), and one intranasally (IN)-vaccinated with the PRRSV-2 vaccine (IL).ResultsClinical, pathological, and immunological outcomes were assessed post-challenge. Both vaccines significantly (p < 0.05) reduced fever duration (3–5 days less than controls, respectively), reduced the clinical scores after challenge, and mitigated weight loss (p < 0.05), though viral loads in serum and lungs remained comparable across groups. Macroscopic lung lesions at 10 days post-challenge (DPC) were reduced in vaccinated groups (13–14% of pneumonic lung on average in vaccinated groups vs. 35% in NV/Ch), yet microscopic lesions persisted, correlating with lung viral loads at 28 DPC (R2 = 0.54, p < 0.001). None of the tested vaccines achieved an efficient control of the viremia or nasal shedding compared to unvaccinated controls. Cross-reactive cell-mediated responses suggested shared epitopes between PRRSV-1 and PRRSV-2; however, the frequencies of interferon-gamma-secreting cells did not correlate with lesion severity.DiscussionThe IN vaccine demonstrated non-inferiority to IM vaccination in alleviating clinical signs and helped reduce weight losses, however, at later times control of viral replication was lower, underscoring limitations in heterologous protection. The dissociation between systemic immune markers and tissue-specific outcomes highlights the need for strategies targeting tissue-resident immunity. These findings advocate further exploration of mucosal vaccination as a complementary strategy for PRRSV control, particularly under heterologous challenge conditions, while emphasizing the persistent challenges posed by viral diversity and incomplete cross-protection.